Quantum-confined stark effect in the ensemble of phase-pure CdSe/CdS quantum dots. Issue 26 (24th June 2019) - Zhang, Lei; Lv, Bihu; Yang, Hongyu; Xu, Ruilin; Wang, Xiaoyong; Xiao, Min; Cui, Yiping; Zhang, Jiayu
Abstract : The ensemble Stark effect (PL, absorption, and ASE) of phase-pure thick-shell CdSe/CdS QDs was systematically investigated under an electric field. Abstract : Colloidal semiconductor quantum dots (QDs) have recently attracted great attention in electric field sensing via the quantum-confined Stark effect (QCSE), but they suffer from the random local electric field around the charged QDs through the Auger process or defect traps. Here, QCSE in the ensemble of phase-pure wurtzite CdSe/CdS QDs was studied by applying a uniform external electric field. We observed clear field-dependent photoluminescence (PL) and absorption characteristics in thick-shell CdSe/CdS QDs with 11 CdS monolayers (11 MLs) including a pronounced spectral redshift in PL of ∼2.3 nm and absorption of ∼2.1 nm. The time-dependent PL intensity traces implied that the thick-shell QDs were conducive to realize the Stark shift in QD ensembles due to the effective suppression of the main sources of the local field. These findings were in stark contrast to those of moderate-shell (5 MLs) and ultrathick-shell (15 MLs) CdSe/CdS QDs. The measurement value of exciton polarizability was smaller than the theoretical value, which may be influenced by very few exciton traps. Moreover, the amplified stimulated emission also exhibited obvious optical modulations under the electric field with decreased emission intensity and an increased ultrafast lifetime. Finally, the temporal evolution of the multiexciton process in thick-shell CdSe/CdS QDs indicated that the multiexciton state induced a higher energy state near the band edge, which may weaken the QCSE of a single exciton. Therefore, it was demonstrated that efficient field control over the optical properties of these nanomaterials is feasible and this can open up potential applications in field-controlled electro-optic modulators.